2008
DOI: 10.1177/0886109908314324
|View full text |Cite
|
Sign up to set email alerts
|

Depression in African American Women

Abstract: Social work interventions that emphasize culturally relevant services from a strengths-based perspective may be more appropriate than traditional mental health services for African American women who suffer from depression. An examination of the literature on epidemiology, etiology, and use of services for this population highlights the paucity of empirical studies, and an exploration of the treatment literature reveals insufficient application of culturally relevant approaches to African American women. Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…For White mothers, their stress could be explained in part by their depressive symptoms. However, depressive symptoms did not predict Black mothers' stress (Valentino et al 2014), which might be better explained by disparities in income, wealth, and debt (Hamilton and Darity 2017; Pfeffer et al 2013) and could indicate that popular scales validated on White populations are inadequate for measuring Black women's depression (Jones and Ford 2008;Watson and Hunter 2015;Woods-Giscombé and Lobel 2008).…”
Section: Financial Stressmentioning
confidence: 99%
“…For White mothers, their stress could be explained in part by their depressive symptoms. However, depressive symptoms did not predict Black mothers' stress (Valentino et al 2014), which might be better explained by disparities in income, wealth, and debt (Hamilton and Darity 2017; Pfeffer et al 2013) and could indicate that popular scales validated on White populations are inadequate for measuring Black women's depression (Jones and Ford 2008;Watson and Hunter 2015;Woods-Giscombé and Lobel 2008).…”
Section: Financial Stressmentioning
confidence: 99%
“…The study explored the women's models of help-seeking and suggested that, "the way in which helpseeking is conceptualized within health promotion practice may serve to reinforce the invisibility of Black Caribbean women in mainstream mental health services and associated research" (Edge and MacKian, 2010, p. 106). In addition, Jones and Ford (2008) pointed out that the White-dominant, socially constructed identity of the Black woman places Caribbean women at risk of being stereotyped and pathologized when they find the courage to seek treatment. Instead of asking for help, considering personal needs, or speaking out against injustice, the expectation that they will overcome renders Black women silent about emotional distress, which leads to the damage of their self-esteem, personal and intimate relationships, and physical and mental health (Clarke, 2010;Woods-Giscombé, 2010).…”
Section: Overview Of Caribbean Womenmentioning
confidence: 99%
“…Results from several studies support Nolen-Hoeksema's assertion, as these studies largely indicate a positive relationship between women's responses to stress and their exposure to stress and depression. Specifically, these various stressors are associated with traditional female roles (Mirowsky & Ross, 1989;Wilhelm, 2006), lack of social power (Nolen-Hoeksema, 2001), histories of trauma (i.e., physical and sexual abuse; Nolen-Hoeksema, 2006;Nolen-Hoeksema & Hilt, 2009;Waite & Killian, 2009), oppression (Jones & Ford, 2008), and discrimination based on race and gender (Moradi & Subich, 2003;Schulz et al, 2006;Warren, 1997;Williams, 2002). While progress has been made to address depression among women, the burden of depression remains heavy and uneven between women.…”
mentioning
confidence: 99%
“…Additionally, the social determinants of health framework recognize that for Black women, their race, class, gender, and their influences on identity and well-being cannot be separated (Jones & Ford, 2008;Thomas, 2004;Thomas, Witherspoon, & Speight, 2008). Exploring social factors in the context of the social determinants of health takes into account both the individual and the society in which Black women live in order to understand mental health (i.e., depression) as a unique social phenomenon among this population (Larsson, 2015).…”
mentioning
confidence: 99%